Performance and Economic Characteristics of Broilers Fed Varying Dietary Levels of Neem Leaf Meal (Azadirachta indica) - Shankar, B.P.; Gowda, R.N.S.; Pattnaik, B.; Prabhu, B.H. Manjunath; Patil, S.S.; Pradhan, H.K. (International Journal of Poultry Science, 2009)
The performance and economic indices of broilers fed varying dietary levels of sun dried Neem Leaf Meal (NLM) were investigated using ninety ‘Ross’ unsexed two weeks old broilers. The birds were randomly assigned to five treatment groups of eighteen birds each in which NLM was incorporated at 0, 0.5, 1.0, 1.5 and 2% for treatments 1, 2, 3, 4 and 5 respectively. Each treatment was further replicated twice with nine birds per replicate in a Completely Randomized Design. Results showed that treatment effect on Average Final Body Weight (AFBW), Average Daily Gain (ADG), Average Daily Feed Intake [ADFI] and Feed Conversion Ratio (FCR) were significant (P<0.05). Birds on the 0.5% NLM had significantly (P<0.05) superior AFBW, ADG and FCR. ADFI of birds on the 0.5% NLM was statistically the same with the control birds but differed from the rest treatments on NLM. Gross margin analysis reveals that a profit of N707.30 is made per bird on the 0.5% NLM as against N630.97, N620.73, N621.81 and N507.06 for birds on the control, 1.0, 1.5 and 2.0% NLM respectively. It is concluded that inclusion of 0.5% NLM in the diets of broilers will support optimum performance and economic benefit.